Flower and Food: Pemanfaatan Elemen Floral dalam Bisnis Kuliner - Ni Ketut Iswarini; I Gusti Ayu Putu Wita Indrayani (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
Floral art has become an interesting element in the world of culinary arts because it can provide a unique and refreshing aesthetic touch to dishes and buffet table decorations. This article examines the use of floral elements in the culinary businesses and explores the trends and potentials associated with their use. Through a qualitative approach, this study identifies phenomena related to the use of floral elements in the culinary arts, including trends in the use of flowers as food and decoration ingredients, challenges in ensuring dish hygiene, and the potential to create unique and unforgettable culinary experiences. Data were collected through literature studies, observation, and unstructured interviews to determine consumer perceptions of the integration of floral elements for decorating dishes and serving rooms. Through a deep understanding of the use of floral art in culinary business, it is hoped that this article can provide insight for chefs, restaurateurs, and culinary enthusiasts to create interesting and innovative dishes that are reinforced with floral elements as decorative elements.